Correlations among measures of quality in HIV care in the United States: cross sectional study. Issue 7629 (29th October 2007) - Wilson, Ira B; Landon, Bruce E; Marsden, Peter V; Hirschhorn, Lisa R; McInnes, Keith; Ding, Lin; Cleary, Paul D
Abstract : Objective To determine whether a selected set of indicators can represent a single overall quality construct. Design Cross sectional study of data abstracted during an evaluation of an initiative to improve quality of care for people with HIV. Setting 69 sites in 30 states. Data sources Medical records of 9020 patients. Main outcome measures Adjusted performance rates at site level for eight measures of quality of care specific to HIV and a site level summary performance score (the number of measures for which the site was in the top quarter of the distribution). Results Of 28 site level correlations between measures, two were greater than 0.40, two were between 0.30 and 0.39, four were between 0.20 and 0.29, and the 20 remaining were all less than 0.20. One site was in the top quarter for seven measures, but no sites were in the top quarter for six or eight of the measures. Across the eight quality measures, sites were in the top quarter no more often than predicted by a chance (binomial) distribution. Conclusions The quality suggested by one measured indicator cannot necessarily be generalised to unmeasured indicators, even if this might be expected for clinical or other reasons.